Inclusive leadership and team creativity: a moderated mediation model of Chinese talent management. Issue 21 (22nd November 2022) - Jia, Jianfeng; Jiao, Yuxin; Han, Hongmei
Abstract: In this study, we examine the impact of inclusive leadership—being open, available, and accessible—on team creativity. Based on componential theory of creativity, we propose a moderated mediation model in which (a) inclusive leadership promotes team creativity, (b) team empowerment mediates the positive relationship between inclusive leadership and team creativity, and (c) HRM system strength enhances the effect of team empowerment. Our hypotheses are supported by analysis of multiple-source data from 91 team leaders and 308 individual members in China. We discuss implications for leadership and talent management.